Distance in Partial Metric Spaces and Common Fixed Point Theorems - Gajanan Dhanorkar, Vidhyadhar Nalawade, Kavthekar Nirmala (Mathematical Statistician and Engineering Applications, 2023)
In this paper, we have proved some results of fixed point on partial metric spaces.